Genome-wide identification, expression analysis and evolutionary relationships of the IQ67-domain gene family in common wheat (Triticum aestivum L.) and its progenitors - Qinglin Ke; Huifan Sun; Minqiang Tang; Ruihan Luo; Yan Zeng; Mengxing Wang; Yihan Li; Zhimin Li; Licao Cui (BMC Genomics, 2022)
Abstract Background The plant-specific IQ67-domain (IQD) gene family plays an important role in plant development and stress responses. However, little is known about the IQD family in common wheat (Triticum aestivum L), an agriculturally important crop that provides more than 20% of the calories and protein consumed in the modern human diet. Results We identified 125 IQDs in the wheat genome and divided them into four subgroups by phylogenetic analysis. The IQDs belonging to the same subgroup had similar exon–intron structure and conserved motif composition. Polyploidization contributed significantly to the expansion of IQD genes in wheat. Characterization of the expression profile of these genes revealed that a few T. aestivum (Ta)IQDs showed high tissue-specificity. The stress-induced expression pattern also revealed a potential role of TaIQDs in environmental adaptation, as TaIQD-2A-2, TaIQD-3A-9 and TaIQD-1A-7 were significantly induced by cold, drought and heat stresses, and could be candidates for future functional characterization. In addition, IQD genes in the A, B and D subgenomes displayed an asymmetric evolutionary pattern, as evidenced by their different gain or loss of member genes, expression levels and nucleotide diversity. Conclusions This study elucidated the potential biological functions and evolutionary relationships of the IQD gene family in wheat and revealed the divergent fates of IQD genes during polyploidization.